International environmental negotiations and non-exclusive domestic property rights - Ernst Mohr (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1990)
A folk theorem in environmental economics suggests that in the presence of transboundary environmental spillovers international negotiations may improve on environmental quality. More so, if side-payments according to the victim-pays principle are undertaken, environmental safeguards agreed upon by the parties to an international agreement can be optimal from the point of view of a global social planner. Implicitly, this folk theorem makes an important assumption: All requirements emanating from the stipulations of an international environmental agreement are smoothly and completely executed within the home countries of the parties to the contract, or so the story goes. However, this presumption is not necessarily fulfilled. In particular, the execution of what the agreement requires from the parties involved may be severely thwarted by either of three reasons.
Keywords: 330; Umweltökonomik; Verhandlungen; Eigentumsrechtstheorie; Theorie